Glacial geomorphology of the Chirripó National Park, Costa Rica - Adolfo Quesada-Román; Juan Antonio Ballesteros-Cánovas; Markus Stoffel; José Juan Zamorano-Orozco (Journal of Maps, 2019)
Several regions of tropical America show imprints of past glacial activity. These relict landforms can support the understanding of past climate conditions, such as during the Last Glacial Maximum (LGM), and the implications that these paleoclimatic conditions could have had on landscape change. Here, we present and analyze glacial morphologies for the Chirripó National Park in Costa Rica based on aerial imagery (1:25,000), detailed Digital Elevation Models, geomorphic mapping, as well as geomorphic assessments in the field to determine and validate landforms. This study adds valuable insights into the reconstruction of the maximum expansion of tropical glaciation during the LGM in Costa Rica and into tropical America glacial landscapes in general.